Prevalence and Risk Factors of Asthma in Preschool Children in Shanghai, China: A Cross-Sectional Study - Ren, Jie; Xu, Jing; Zhang, Pingbo; Bao, Yixiao (Frontiers in Pediatrics, 2022)
Background: Previous studies have shown the increasing prevalence of childhood asthma around the world as well as in China. Nevertheless, little is known about the epidemiology of asthma in preschool children. Thus, the present study investigated the prevalence and severity of asthma in Shanghai, China, and identified related risk factors for asthma in children at the age of 3-6. Methods: Information was obtained through the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Risk factor analysis was carried out using univariate and multivariate logistic regression. Results: A total of 6183 children (3165 boys and 3018 girls) covering 12 communities were included in our study, with an average age of 4.2±0.7 years. The prevalence of ever asthma, current asthma and physician-diagnosed asthma was 16.0%, 11.2% and 5.3%, respectively. Parental allergic history, including rhinitis, asthma, and eczema, was significantly associated with current asthma. The strongest association with current asthma was paternal asthma (aOR=6.21, 95% CI 4.08-9.45), and maternal asthma had the second strongest association with current asthma (4.11; 2.56-6.57). Among personal factors, food allergy history, antibiotic use and paracetamol use in the first year of life were significantly associated with current asthma (aOR=1.90, 95% CI 1.56-2.31; aOR=1.54, 95% CI 1.26-1.89; aOR=1.22, 95% CI 1.00-1.48, respectively). More than once paracetamol use per year and per month were both associated with current asthma in a dose-response manner. Additionally, female sex was an independent protective factor (aOR=0.82, 95% CI 0.69-0.98). Among environmental factors, dampness or mildew at home was an independent risk factor for current asthma (aOR=1,60, 95% CI 1.19-2.14). Furthermore, dampness or mildew, infrequent house cleaning, and truck traffic in residential streets were significantly associated with asthma symptoms only in old communities, while paracetamol use in the first year of life and flooring materials were significant factors only in new communities. Conclusion: The prevalence of asthma has increased among preschool children in Shanghai over the past three decades. The identified risk factors indicated the combined effects of genetic, personal and environmental factors on asthma symptoms. Differentiated strategies should be taken for preventing asthma in old and new communities.